Determination of somatotype and physical activity level in frailty older adults - Suélen Gomes dos Santos Marques; Rodrigo Villar; Liliane de Faria Marcon; Gustavo Allegretti João; Roberta Luksevicius Rica; Danilo Sales Bocalini; Francisco Luciano Pontes Júnior (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To determine the somatotype profile and level of physical activity in older adults. Methods: Seventy-two older adults were divided into two groups: frail (F = 33) and non-frail (NF = 39). Frailty status was determined using the Tilburg Frailty Indicator (TFI), somatotype using the Heath and Carter method, and physical activity by the International Physical Activity Questionnaire (IPAQ). Results: Somatotype analysis showed a predominance of endomorphy (F = 6.54 ± 1.65 vs NF = 6.12 ± 2.07 p ≤ 0.350) followed by mesomorphy (F = 3.44 ± 1.62 vs NF = 3.15 ± 2.19, p ≤ 0.531) and ectomorphy (F = 0.82 ± 0.99 vs NF = 0.95 ± 0.86 p ≤ 0.163), but no significant differences were observed between groups. Regarding PA, twenty-eight participants (84.7%) of the F group were classified as sedentary and insufficiently active and twenty-one (53.8%) of NF were classified as active and very active. This difference in PA explains the higher total energy expenditure found in NF (median 1,087.43; IAQ = 3,954.30) when compared to F (median = 0.0; IAQ = 462.64 p ≤ 0.001). The frailty group presented a higher endomorphic component as well as lower levels of physical activity and energy expenditure. Conclusion: Endomorphy was the predominant somatotype in F and NF older adults, followed by mesomorphy and actomorphy this profile can affect activities of daily living, functional capacity, and independent living and be associated with chronic diseases.